Helminths of eight anuran species from a remnant riparian forest in the cerrado biome, Brazil - Queiroz, Murilo S. [UNESP]; Pontes, Mariana R.; Neto, Marcos C. [UNESP]; Campião, Karla M.; Anjos, Luciano A. [UNESP] (My University, 2020)
Parasites are important organisms in the ecosystem’s functions and it is an overlooked biodiversity, in areas severely affected by human activities, e.g. Brazilian Cerrado, most of its species often disappear without them having been reported. Considering the current knowledge gap between parasite-host relationships, studies that increase understanding about these relationships become relevant. Here, we provide more information about the geographical distribution, life cycle and host records of helminth species associated with eight anuran species in Cerrado. Hosts were collected by pitfall traps and scan searching method in the riparian forest of Véstia’s stream, Selvíria, Mato Grosso do Sul state. We found a total of 16 helminth taxa: nine species of Nematoda, six species of Trematoda and one species of Acanthocephala. We report 15 new host records and a new geographical distribution for some parasite species, emphasizing the importance of parasitological surveys to increase knowledge about diversity of parasite species and the search for new species. Wildlife inventories, descriptions of species and helminth fauna revisions are necessary because they enhance our understanding of parasitism in vertebrate groups and build a baseline for further studies.
Keywords: Amphibian; Biology Conservation; Herpetoparasitology; Hylidae; Leptodactylidae; Mato Grosso do Sul State; Parasites